Technological accelerator with closed electron drift for surface treatment - Goncharov, A.A.; Dobrovolskii, A.M.; Pavlov, S.N.; Panchenko, O.A.; Protsenko, I.M. (Вопросы атомной науки и техники, 2000)
Now the technologies of functional covers deriving on large surfaces intensively are developed. For these purposes the plasma sputtering systems of magnetron, vacuum - arc, electron -beam and other types are effectively used. The quality of cover largely depends on preliminary treatment of a surface - its clearing and activation. In the paper is shown, that the anode layer thruster (or the anode layer accelerator – ALA) intensively cleans a surface of target body in a narrow pressure range of working gas in a system. On absolute rate of cleaning (~ 1 nm/s) ALA do not concede to a Kaufman sources. The injection of gas in the accelerator through electrodes with success can be replaced by injection immediately in volume. In this case the rates of sputtering increase approximately twice. The optimal pressure for cleaning essentially will increase, that does ALA compatible with a magnetron on pressure of working gases.